Strategi Pengembangan Sistem Operasi Windows untuk Memperkuat Proteksi Windows terhadap Ancaman Malaware - Rakhmadi Rahman; M. Faiz Ilyas; Muhammad Alfarizky Yusuf (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Behind the widespread proliferation of malware, IT experts have developed robust security systems to minimize the risk of malware infection. In the Windows security system, numerous software solutions have been created to prevent malware threats, including Windows Defender, which serves as the core of Windows security, virus & threat protection, real-time protection, firewall & network protection, account protection, and many more. This study uses a qualitative approach based on literature review. The results indicate that by integrating machine learning technology, enhancing security features, and adopting a layered approach, the strategy for developing the Windows operating system has successfully strengthened protection against malware threats. These measures not only improve the ability to detect and respond to threats but also ensure that users can enjoy a safe and protected computing experience.